POTENSI EKONOMI DAN ARAHAN PENGEMBANGAN PEREKONOMIAN WILAYAH DI DESA-DESA PENYANGGA TAMAN NASIONAL UJUNG KULON - Tb Iwan Mulyawan; Baba Barus; Muhamad Firdaus (Jurnal Ilmu Tanah dan Lingkungan, 2015)
Sumur District and Cimanggu District are the buffer areas of Ujung Kulon National Park (UKNP). Based on the Spatial Planning of Pandeglang Regency 2013, the districts were designated as the center development of trade and services. In fact, there is still a lack of infrastructure. This condition is the main problem of the regional development plan. This study aims to: (1) analyze the village hierarchy based on areas for Sumur District and Cimanggu District; (2) analyze the main sector that supports the regional development; (3) propose the economic development programs in Sumur District and Cimanggu District. The results show that are twelve (12) UKNP buffer villages in hierarchy III. In hierarchy III, where there are five villages that have a relatively high economically disadvantaged population (79.9% - 87.8%). There are six villages in hierarchy II, and only one village in hierarchy I. The main sector in Sumur District, are rice (wet cultivation), vegetables, ornamental plants, livestock, fisheries and tourism. The main commodities in Cimanggu District, are rice, crops, vegetables, livestock, and plantations. The recommendation of regional development in Sumur District is fishery and tourism, the program of modern fishing technology, construction of ports and financial/capital institutions, facilities and infrastructure for tourism. The recommendation of regional development in Cimanggu District is on agriculture and plantation, the program of agricultural technology, financial/capital institutions, facilities and infrastructure to support the local economy. Keywords: Area development, area hierarchy, pandeglang, the potential of buffer areas in TNUK